2019
DOI: 10.1186/s12970-019-0291-x
|View full text |Cite
|
Sign up to set email alerts
|

Creatine electrolyte supplement improves anaerobic power and strength: a randomized double-blind control study

Abstract: Background Creatine supplementation aids the Phosphagen system by increasing the amount of free creatine and phosphocreatine available to replenish adenosine triphosphate. The purpose of this study was to investigate the effects of a creatine and electrolyte formulated multi-ingredient performance supplement (MIPS) on strength and power performance compared to a placebo. Maximal strength along with total concentric work, mean rate of force development (mRFD), mean power, peak power, and peak force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…For example, Wang et al (2018) reported that creatine supplementation combined with exercise training for 4 weeks improved maximal muscular strength and reduced exercise-associated muscle damage in adults. Furthermore, oral consumption of creatine electrolyte improved overall and repeated short duration sprint cycling performance (Crisafulli et al 2018), as well as anaerobic power and strength in athletes (Hummer et al 2019).…”
Section: Health Benefits Of Creatine Supplementationmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, Wang et al (2018) reported that creatine supplementation combined with exercise training for 4 weeks improved maximal muscular strength and reduced exercise-associated muscle damage in adults. Furthermore, oral consumption of creatine electrolyte improved overall and repeated short duration sprint cycling performance (Crisafulli et al 2018), as well as anaerobic power and strength in athletes (Hummer et al 2019).…”
Section: Health Benefits Of Creatine Supplementationmentioning
confidence: 95%
“…By delaying the depletion of ATP during oxygen deprivation and reducing the availability of ROS (Balestrino et al 1999), pretreatment with creatine can reduce the cardiac and neurological damages induced by ischemia or anoxia and that such treatment can also be useful even after the onset of stroke or myocardial infarction (Balestrino et al 2002;Lensman et al 2006;Osbakken et al 1992;Perasso et al 2013;Prass et al 2007;Scheer et al 2016;Shen and Goldberg 2012;Whittingham and Lipton 1981;Wilken et al 1998;Zapara et al 2004). Of note, creatine has been safely and beneficially administered to patients affected by age-related neurological diseases, including Parkinson's disease, Huntington's disease, amyotrophic lateral sclerosis, long-term memory deficits, Alzheimer's disease, and stroke (Adhihetty and Beal 2008; Smith et al 2014), as well as patients with pathophysiological conditions, such as gyrate atrophy, post-stroke depression, congestive heart failure, chronic musculoskeletal pain disorders, atherosclerotic diseases, and cisplatin-induced renal damage (Genc et al 2014;Hummer et al 2019;Persky and Brazeau 2001;Wyss and Schulze 2002). Through increasing the availability of arginine for the generation of nitric oxide (a killer of pathogenic bacteria, fungi, parasites, and viruses), dietary supplementation with creatine plays an important role in protecting humans from infectious diseases (Ren et al 2018).…”
Section: Health Benefits Of Creatine Supplementationmentioning
confidence: 99%
“…When physical exercise is performed for a certain amount of time, ATP levels are reduced and physiologically recomposed through the CrP molecules, but if the physical stimulus is maintained, the stock of CrP is reduced. 18,19,20 According to studies conducted involving the ingestion of creatine in two phases, one of loading and the other of maintenance, a 20% increase in muscle creatine levels was found. 21,22 This fact could favor maintaining the CrP levels and improve the fatigue threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Marine omega 3 (eicosapentaenoic acid -EPA, and docosahexaenoic acid -DHA), iron, zinc, vitamin B12, calcium, vitamin D and creatine are some potentially restricted nutrients in these diets, since their primary sources are derived from animals [2,3] Some nutrients are directly or indirectly linked to exercise performance and recovery from physical effort [4][5][6], with emphasis on creatine. This nutrient plays an important role in energy metabolism, especially about exercise of maximum intensity and short duration, using mainly the anaerobic route [7,8]. In this way, the phosphocreatine reserves in the muscle are dephosphorylated, with the donation of a molecule free of inorganic phosphate (P) to the adenosine diphosphate molecule (ADP), to resuscitate ATP.…”
Section: Introductionmentioning
confidence: 99%